PENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR AL-QUR’AN MENGGUNAKAN ALAT PERAGA REALIA - Ratnika Wati (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2021)
This study aims to increase student activity and learning achievement in learning Islamic Religious Education (Pendais) Alquran in Class V students of SDN 4 Sawah Lama Bandar Lampung TP 2019/2020. This research applies Classroom Action Research to take action in three learning cycles, each of which consists of planning, acting, observing, reflecting. Research time for the first semester of the 2019/2020 academic year, the subjects consisted of 30 Class V students. Research data were taken from activity observations, final cycle tests, and peer teacher observations. Data analysis used simple percentages. The results of the study of learning activities in cycle I an average of 68.5%, cycle II an average of 87.5%, cycle III an average of 99.5%. Achievement of learning outcomes (completeness): Complete cycle I 64%, Cycle II completed 84%, Cycle III completed 97%. Based on the results of research and discussion, it can be concluded that the use of realia teaching aids can increase the activity and learning achievement of Islamic Religious Education (Pendais) Al-Qur'an in Class V Students of SDN 4 Sawah Lama Bandar Lampung TP 2019/2020.